Small‐Molecule Inhibitors of the Tumor Suppressor Fhit. (20th July 2017) - Lange, Sandra; Hacker, Stephan M.; Schmid, Philipp; Scheffner, Martin; Marx, Andreas
Abstract: The tumor suppressor Fhit and its substrate diadenosine triphosphate (Ap3 A) are important factors in cancer development and progression. Fhit has Ap3 A hydrolase activity and cleaves Ap3 A into adenosine monophosphate (AMP) and adenosine diphosphate (ADP); this is believed to terminate Fhit‐mediated signaling. How the catalytic activity of Fhit is regulated and how the Fhit⋅ Ap3 A complex might exert its growth‐suppressive function remain to be discovered. Small‐molecule inhibitors of the enzymatic activity of Fhit would provide valuable tools for the elucidation of its tumor‐suppressive functions. Here we describe the development of a high‐throughput screen for the identification of such small‐molecule inhibitors of Fhit. Two clusters of inhibitors that decreased the activity of Fhit by at least 90 % were identified. Several derivatives were synthesized and exhibited in vitro IC50 values in the nanomolar range. Abstract : High‐throughput screening for enzyme inhibitors : Small‐molecule inhibitors that suppress enzymatic hydrolysis of diadenosine triphosphate (Ap3 A) into AMP and ADP by the human tumor suppressor Fhit have been identified and developed by high‐throughput screening and organic synthesis.